2013
DOI: 10.1111/jphp.12090
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids as a source of potential anticholinesterase inhibitors for the treatment of Alzheimer's disease

Abstract: Objectives The inhibition of acetylcholinesterase (AChE), the key enzyme in the breakdown of acetylcholine, is currently the main pharmacological strategy available for Alzheimer's disease (AD). In this sense, many alkaloids isolated from natural sources, such as physostigmine, have been long recognized as acetyl-and butyrylcholinesterase (BChE) inhibitors. Since the approval of galantamine for the treatment of AD patients, the search for new anticholinesterase alkaloids has escalated, leading to promising can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(110 citation statements)
references
References 155 publications
3
81
0
13
Order By: Relevance
“…2011). Since the approval of galantamine for the treatment of AD patients, the search for new anticholinesterase alkaloids has escalated, leading to promising candidates, such as huperzine A (Konrath et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2011). Since the approval of galantamine for the treatment of AD patients, the search for new anticholinesterase alkaloids has escalated, leading to promising candidates, such as huperzine A (Konrath et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is a centrally acting, selective, reversible, and competitive AChEI, as well as from an allosteric modulator of the neuronal nicotinic receptor for acetylcholine, improving cholinergic transmission. Interestingly, it has shown to be protective in different models related to AD, ischemia, Huntington's disease, or amyotrophic lateral sclerosis (ALS) [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly to AD, a multitude of studies have shown that they act as prominent brain health improvers, being useful not only to prevent but also to block and even avert neurological dysfunctions (Marco and Carreiras 2006;Essa et al 2012;Smid et al 2012;Spencer et al 2012;Konrath et al 2013;Ahmed et al 2015). Furthermore, it is convenient to highlight that the majority of chemical drugs are plant-derived mimetic; notwithstanding, in the whole plant, different proportions of phytochemicals, their synergisms, antagonisms, and polyvalent reactions improve the bioactive potential and also block some harmful substances.…”
Section: Introductionmentioning
confidence: 99%